PERANCANGAN KOMUNIKASI VISUAL PROMOSI PESANTREN AR-RISALAH MELALUI MEDIA UTAMA BALIHO - Yusri .; Lisa Widiarti; Abd. Hafiz (DEKAVE : Jurnal Desain Komunikasi Visual, 2012)
Abstract The purpose of the writing of this final project report is to motivate society of the existance of Ar-Risalah boarding school, which is located Air Dingin RT 01, RW 09, Kelurahan Balai Gadang, Kec. Koto Tangah, Padang. The use of billboard as the main media, is because it is effective as a promotion media. Besides, the writer also designs other media, such as brochure, pin, keychains, x banner, poster, id card, sticker, bookmark, and pamflet. Kata Kunci: Promosi, Pesantren, Baliho